Endoscopic-ultrasound versus percutaneous-guided celiac plexus block for chronic pancreatitis pain. A systematic review and meta-analysis - Nobre Moura, Renata (2017)
Background: Abdominal pain is present in the vast majority of patients with chronic pancreatitis, being frequently debilitating. Celiac plexus block (CPB) is an interventional technique that can be considered to provide a temporary pain relief. Objective: To estimate the effectiveness and safeness of endoscopic-ultrasound (EUS) comparing with percutaneous-guided CBP in patients with pancreatic pain. Methods: A systematic review of English and non-English articles using MEDLINE, EMBASE, LILACS and COCHRANE (via BVS). Study selection and data extraction: Only randomized control trials (RCT) comparing the beneficial and harmful effects of EUS and percutaneous-guided celiac plexus block for managing pancreatic pain were included. Data was extracted and analyzed on variables including pain relief and related procedure complications. Results: Two RCT met the inclusion criteria. Both studies assessed the primary outcome (reduction on pain score) and evaluated adverse effects. The drugs injected were the same; nevertheless percutaneous technique was guided by fluoroscopy in one study and by computer tomography (CT) in other. The results showed that the EUS-CPB group was more effective to reduce pain score after 4 weeks after the procedure, with risk of bias to do this affirmation. No statistical difference in pain relief at 1, 8 and 12 weeks and in complications rates. Conclusions: Based on this systematic review and meta-analysis, no statistically significant difference was noted in pain relief and complications for EUS and percutaneous - CPB.